Implementation in largest consistent set via rights structures - Korpela Ville; Lombardi Michele; Vartiainen Hannu (Elsevier, 2022)
The designer's exercise consists of designing a rights structure that formalizes the idea of power distribution in society. A solution is implementable in largest consistent set by a rights structure if there exists a rights structure such that for each preference profile, the largest consistent set of the game played by agents coincides with the set of outcomes that the solution would select for it. In a setting with transfers, every Maskin monotonic solution is implementable. This finding implies that the class of implementable solutions in core equilibria is unaltered by farsighted reasoning.